1982
DOI: 10.1111/j.1469-8137.1982.tb03388.x
|View full text |Cite
|
Sign up to set email alerts
|

A Histochemical Study of Bud Initiation in the Brown Alga Sphacelaria Furcigera*

Abstract: SUMMARYPrevious ultrastructural studies of Sphacelaria furcigera have revealed the existence of distinct ' morphological' layers within the outer longitudinal cell walls. Bud initiation and development from an axial mother cell involve a change in the layering pattem. The histochemical evidence suggests that the cell wall is composed primarily of alternating layers of sulphated polysaccharides (fucans) and acidic polysaccharides (alignates). Structural integrity of the developing bud cell wall appears to be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The existence of alginates in brown algal cell walls has been confirmed by differential, histochemical staining and indicated to be localized in particular layers of the cell walls (McCully 1966;Evans and Holligan 1972;Burns et al 1982). Alginic acid is composed of three different oligosaccharides, mannuronic acid (M) blocks, guluronic acid (G) blocks, and blocks with alternating mannuronic and guluronic (MG) units (Haug et al 1974).…”
Section: Discussionmentioning
confidence: 96%
“…The existence of alginates in brown algal cell walls has been confirmed by differential, histochemical staining and indicated to be localized in particular layers of the cell walls (McCully 1966;Evans and Holligan 1972;Burns et al 1982). Alginic acid is composed of three different oligosaccharides, mannuronic acid (M) blocks, guluronic acid (G) blocks, and blocks with alternating mannuronic and guluronic (MG) units (Haug et al 1974).…”
Section: Discussionmentioning
confidence: 96%
“…In Sphacelaria furcigera , bud (branch) formation was observed (Burns et al. 1982a,b). The axial cell wall is composed of four layers (CW1–CW4), but the initial bud region is covered by two newly synthesized layers (CWO and CWI).…”
mentioning
confidence: 99%
“…Burns et al. (1982a) suggested that alginates are abundant in CW2, CW4, and CWI, while sulfated fucans were prominent in CW1, CW3, and CWO. Cell wall structure on the rhizoid tip in fucoid zygotes has been observed (Novotny and Forman 1975, Callow et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation